2015
DOI: 10.1186/s13104-015-1441-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple alignment comparison of the non-structural genes of three strains of equine influenza viruses (H3N8) isolated in Morocco

Abstract: BackgroundThree equine influenza viruses, A/equine/Nador/1/1997(H3N8), A/equine/Essaouira/2/2004(H3N8), and A/equine/Essaouira/3/2004(H3N8), were isolated from different Equidae during local respiratory disease outbreaks in Morocco in 1997 and 2004. Their non-structural (NS) genes were amplified and sequenced.ResultsThe results show high homology of NS nucleotide sequences of A/equine/Nador/1/1997 with European strains (i.e., A/equine/newmarket/2/93 and A/equine/Grobois/1/1998) and clustered into the European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Even when the antigenic drift in HA and NA is the most important mechanism for influenza virus evolution and drives the divergence of lineages, the conservation of viral fitness requires an optimal interaction between the proteins encoded by all the genomic segments (19). However, there are only a few studies in EIV that have analyzed the other genomic segments (6,10,12,20,21).…”
mentioning
confidence: 99%
“…Even when the antigenic drift in HA and NA is the most important mechanism for influenza virus evolution and drives the divergence of lineages, the conservation of viral fitness requires an optimal interaction between the proteins encoded by all the genomic segments (19). However, there are only a few studies in EIV that have analyzed the other genomic segments (6,10,12,20,21).…”
mentioning
confidence: 99%
“…Sequencing of three H3N8 isolates from Morocco namely A/equine/Nador/1/1997, A/equine/Essaouira/2/2004 and A/equine/Essaouira/3/2004 showed that A/equine/Nador/1/1997 had relatedness with European lineage while A/equine/Essaouira/2/2004 and A/equine/Essaouira/3/2004 had homology with A/equine/Fontainbleu/1/1979. A/equine/Essaouira/2/2004 and A/equine/Essaouira/3/2004 also showed 12 substitutions in NS1 protein when compared with the reference A/equine/Miami/1963 strain (Boukharta et al, 2015 ).…”
Section: Epidemiology and Evolutionmentioning
confidence: 99%
“…The BLAST alignment followed by phylogenetic analysis of the partial NS gene sequences showed that the isolates recovered from 2004 and 1997 were closely related and were in circulation before 1990. Interestingly, the three isolates shared the same ancestry without any genetic reassortment [224].…”
Section: Moroccomentioning
confidence: 99%